Optimasi Pembuatan Tricalcium Phospate (TCP) Berpori Dengan Metode Protein Foaming-Starch Consolidation Menggunakan Analisa Response Surface Methodology (RSM) - Adi Maulana Putra; Ahmad Fadli; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Porous Tricalcium phosphate is a material that can be used as bone substitute. Protein foaming-starch consolidation method is a technique to produce Porous Tricalcium Phosphate (TCP) using yolk as an agent to form pore. This research aims to know the influence of slurry composition and temperature rising rate of sintering on physical, chemical and mechanical properties of porous TCP and to conduct characterization porous TCP in accordance with standard as synthetic bone graft. This research was begun with mixing the TCP powder, starch, Darvan 821A and yolk. Slurry was stirred mechanically in speed of 150 rpm for 3 hours. Slurry was poured in mold and heated in oven with the temperature of 180°C for an hour. Then sample was released from mold and burnt at 600°C ended by sintering at 1100°C for an hour. The result was porous TCP with porousity of 73,7-79,30%, density of 0,65-0,83 g/cm3 and compressive strength of 1,88-2,4 Mpa. Significance level between variables can be seen from pvalue < 0,05 and lack of fit > 0,05 which show that model was corresponding toward the result. R2 obtained were Y1 = 89,68%, Y2 = 89,69%, Y3 = 89,06%. The most affecting factor significantly towards all the responses was dispersant addition that followed by starch addition and temperature rising rate of sintering. In optimum condition (dispersant addition of 8,09 gr with starch addition of 9 gr and temperature rising rate of sintering of 1°C/minute) was obtained the optimum value of response for porosity by 75,7378%, density by 0,76gr/cm3 and compressive strength 2,16 Mpa.Keywords : tricalcium phophate, yolk, porosity, density, compressive strength